Determinants of capital structure in Irish SMEs - LUCEY, BRIAN MICHAEL (Springer, 2010)
This paper presents an empirical examination of determinants of the capital structure of a sample of 299 Irish small and medium-sized enterprises (SMEs). Results suggest that age, size, level of intangible activity, ownership structure and the provision of collateral are important determinants of the capital structure in SMEs. A generalisation of Zellner?s (Journal of the American Statistical Association 57, 348?368, 1962) seemingly unrelated regression (SUR) approach is used to examine industry effects and to test the stability of parameter estimates across sectors. We find that the influence of age, size, ownership structure and provision of collateral is similar across industry sectors, indicating the universal effect of information asymmetries. Firms overcome the lack of adequate collateralisable firm assets in two ways: by providing personal assets as collateral for business debt, and by employing additional external equity to finance research and development projects.
PUBLISHED
Keywords: Economics; Capital Structure